Oocyte central granularity and its relation to pregnancy outcome following intracytoplasmic sperm injection-freeze-all cycles - Gupta, Aakriti; Vargese, Alex C.; Ashraf, Mohamed C.; Binoy, Dhannya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Oocyte quality is instrumental in the development of early embryos and may account for the difference in the rates of fertilization, cleavage, implantation and pregnancy outcome. Centrally located cytoplasmic granularity is a rare morphological feature that can be observed in certain cases. We conducted this study with the sole aim to compare the pregnancy outcomes from embryo derived exclusively from oocytes with dense central granularity with embryos derived from oocytes with normal morphology in intracytoplasmic sperm injection (ICSI)-freeze- all cycles. Methods: A retrospective case control study performed during a period of 1 year and 10 months from Jan 2018-Oct 2019 at craft hospital and research centre India; a tertiary heath care centre. The 62 infertile women undergoing ICSI FET cycle with oocyte cohort having all central granularity oocytes were included as study participants after fulfilling the inclusion and exclusion criteria. The 200 women undergoing ICSI- frozen embryo transfer (FET with normal morphology oocyte were taken. Implantation rate and clinical pregnancy rate were evaluated as primary outcomes. Ongoing pregnancy rate, live birth rate, fertilization rate and top-quality embryo were taken as secondary outcomes. Results: The implantation rate and clinical pregnancy rate was 21.48% and 40.33% in study group compared to 35.012% and 58.5% respectively in control group which was statistically significant (p=0.002; 0.012 respectively). Conclusions: Presence of dense central granularity in the oocyte can be used to predict poor ART outcome in terms of low implantation and clinical pregnancy rates.